Utilizing the surface potential of a solid electrolyte region as the potential reference in Kelvin probe force microscopy - Ishida, Nobuyuki (Beilstein Journal of Nanotechnology, 2022)
In electrochemical measurements, monitoring the electrode potential using a stable reference is essential for controlling the redox reactions that occur at the electrodes. In Kelvin probe force microscopy (KPFM) measurements on electrochemical cells, the surface potential is generally measured relative to electrical ground instead of a stable reference. Here, we show that the changes in the surface potential, measured using KPFM relative to the surface potential in the electrolyte region, is consistent with the changes in the electrode potential measured using a voltmeter relative to a reference electrode. These results demonstrate that the surface potential in the electrolyte region can be utilized as a stable potential reference when analyzing KPFM data.
Keywords: electrochemistry; Kelvin probe force microscopy (KPFM); reference electrode; solid electrolyte